Perceptions of Teaching Staff Regarding Time Management in Making Students' Learning More Efficient - Lăcrămioara Popescu; Adriana Denisa Manea; Cristian Stan (Educaţia 21)
Focusing on time management is essential to making student learning worthwhile. Rigorous time management allows students to discover more controlled than task and activities or activities or daily. Our study aims to investigate teachers' perceptions of managing students' learning time, both in and out of the classroom. Knowing that time management is based on three pillars, namely: planning, organization, and the results of the study highlight the need for students to learn time management with an emphasis on: learning to set priorities, self-monitoring/self-responsibility. management according to a set schedule, the daily distribution of learning times and free time according to one's own needs. At the same time, it is necessary to involve teachers in the formation of effective time management skills and abilities in their students, in order to avoid procrastination. At the same time, the counseling of parents by teachers on the proper management of their children's learning and leisure time is a necessity to make learning more efficient for school-age children.